2022
DOI: 10.1038/s41598-022-18232-6
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 and Alu methylation signatures in autism spectrum disorder and their associations with the expression of autism-related genes

Abstract: Long interspersed nucleotide element-1 (LINE-1) and Alu elements are retrotransposons whose abilities cause abnormal gene expression and genomic instability. Several studies have focused on DNA methylation profiling of gene regions, but the locus-specific methylation of LINE-1 and Alu elements has not been identified in autism spectrum disorder (ASD). Here we interrogated locus- and family-specific methylation profiles of LINE-1 and Alu elements in ASD whole blood using publicly-available Illumina Infinium 450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…ASD is a male-biased disorder that is at least four times more common in males than in females [ 17 ]. The exact cause of ASD is still unclear, but it is thought that both genetic and environmental factors influence ASD [ 10 , 13 , 14 , 18 22 ]. Moreover, recent studies have reported that epigenetic regulatory mechanisms, including DNA methylation [ 19 , 20 , 22 ], histone modifications [ 23 , 24 ], and noncoding RNA-associated gene silencing [ 25 ], are associated with ASD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASD is a male-biased disorder that is at least four times more common in males than in females [ 17 ]. The exact cause of ASD is still unclear, but it is thought that both genetic and environmental factors influence ASD [ 10 , 13 , 14 , 18 22 ]. Moreover, recent studies have reported that epigenetic regulatory mechanisms, including DNA methylation [ 19 , 20 , 22 ], histone modifications [ 23 , 24 ], and noncoding RNA-associated gene silencing [ 25 ], are associated with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…The exact cause of ASD is still unclear, but it is thought that both genetic and environmental factors influence ASD [ 10 , 13 , 14 , 18 22 ]. Moreover, recent studies have reported that epigenetic regulatory mechanisms, including DNA methylation [ 19 , 20 , 22 ], histone modifications [ 23 , 24 ], and noncoding RNA-associated gene silencing [ 25 ], are associated with ASD. Environmental factors that are thought to cause or increase the susceptibility of ASD include BPA and bisphenol-related compounds [ 10 , 13 , 14 , 18 , 26 28 ], polychlorinated biphenyls (PCBs), phthalates [ 29 , 30 ], and cigarette smoke [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…These genes are known to be associated with neurodevelopmental disorders [ 20 , 21 ]. Locus- and family-specific Alu and LINE-1 methylation and the expression level of their host genes were found to be altered in the blood of ASD individuals identified using the Infinium 450 K platform [ 22 ]. Global LINE-1 methylation was significantly decreased in the blood samples from ASD individuals with mental regression [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these sequences belong to ancestral/old LINE-1 subfamilies, such as L1M (mammalian-specific, oldest), no longer mobilize, and are thought to be largely non-functional. Only a small fraction of LINE-1 sequences, including L1HS/L1PA1 (human-specific, youngest) and the young L1PA subfamilies from L1P (primate-specific, intermediate), are of full length and capable of retrotransposition [ 3 ]. A human full-length L1 transcript is 6 kb long and has a 900 nt 5′-untranslated region (UTR) that functions as a RNA polymerase II internal promoter, two open reading frames (ORF1 and ORF2), a short 3′-UTR, and a poly(A) tail.…”
Section: Introductionmentioning
confidence: 99%